2020
DOI: 10.4149/neo_2020_190619n523
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of synuclein-γ levels by novel monoclonal antibody in saliva and cancer tissues from oral squamous cell carcinoma patients

Abstract: The clinical value of synuclein-γ (SNCG) in oral squamous cell carcinoma (OSCC) was evaluated by detecting the expression of SNCG in saliva and tissues and its correlation with clinicopathological parameters (age, gender, ethnicity, degree of differentiation, clinical stage, and lymph node metastasis). Salivary samples were collected from 79 patients with OSCC, 31 patients with oral premalignant lesions (OPMLs), such as oral lichen planus, oral leukoplakia, and erythema, and 80 controls, and levels of SNCG in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…In this study, we explored the expression and role of SNCG in OSCC. First, we detected the mRNA and protein expression of SNCG in OSCC and found that SNCG was highly expressed in OSCC tissues, which was consistent with our previous study [ 24 , 25 ]. And our results were consistent with those reported in multiple articles, which indicate that SNCG was highly expressed in a variety of tumors [ 9 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, we explored the expression and role of SNCG in OSCC. First, we detected the mRNA and protein expression of SNCG in OSCC and found that SNCG was highly expressed in OSCC tissues, which was consistent with our previous study [ 24 , 25 ]. And our results were consistent with those reported in multiple articles, which indicate that SNCG was highly expressed in a variety of tumors [ 9 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, the difference between our experimental results and database results may be due to different sample sources and ethnic differences, which may require more samples to test. At the same time, we analyzed the correlation between the expression of SNCG in OSCC and clinicopathological features and found that the expression of SNCG was related to differentiation, which was consistent with our previous study [ 24 , 25 ]. Next, we explored the diagnostic value of SNCG in OSCC tissues.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…SNCG is elevated in OSCC cells and increases the ability of the human OSCC cells, OEC‐M1, to migrate and invade 10 . Our previous study has confirmed the existence of SNCG in OSCC cells and shown high levels of salivary SNCG in OSCC and OPMD patients 28 . Nevertheless, it cannot distinguish between these two types of patients.…”
Section: Discussionmentioning
confidence: 74%
“…2 mL of fasting whole blood was collected as a blood sample, centrifuged at 1200 g for 10 min at room temperature (RT), and transferred the clear supernatant as the serum sample to sterile test tubes. Subjects were asked to rinse their mouth with water for 5 minutes before the saliva sample was collected.1 ~ 2 mL of saliva was obtained by naturally secreted into the sterile collection tube, the sample was immediately centrifuged at 1000 g for 2 min at RT, and the supernatant was transferred to a sterile sample tube to be mixed with protease inhibitor [15]. All saliva and serum samples were stored in the refrigerator at -80℃.…”
Section: Serum and Saliva Samples Collectionmentioning
confidence: 99%